Balloons, kites, airships, and gliders - Loves, June.; Lucia, Lorenzo (Broomall, PA : Chelsea House Publishers, 2002)
A color-illustrated overview of unusual types of aircraft that describes hot air balloons, airships, kites, hang-gliders, gliders, paragliders, and microlights.
"First published in 2000 by Macmillan Education Australia ... South Yarra, Australia"--T.p. verso.
Includes index.
Library Talk.
5.9
3-6
Keywords: Airships -- Juvenile literature; Balloons -- Juvenile literature; Gliders (Aeronautics) -- Juvenile literature; Kites -- Juvenile literature; Airships; Balloons; Flight; Gliders (Aeronautics); Kites; Airships; Balloons; Flight; Gliders (Aeronautics); Kites